Knee associated problems and functional mobility among adults with knee osteoarthritis - Singh, Devinder Kaur Ajit; Kamsan, Siti Salwana; Ying, Agnes Ngu Chien; Ahmad, Mohd Azzuan; Mohd Padzil, Fazlina @ Asma; Muhammad Hendri, Efri Noor (2017)
Knee osteoarthritis (KOA) is a major cause of disability and significantly reduce quality of life (QOL). Even though KOA is one of the most prevalent musculoskeletal disorders in Malaysia2, there is limited information about knee associated problems and functional mobility among Malaysian adults with KOA. The aim of this study was to examine knee associated problems and functional mobility among KOA population in Malaysia.